Pengaruh Green Lifestyle terhadap Perilaku Konsumen dalam Pembelian Produk Eco Friendly pada Generasi Z di Kalangan Mahasiswa FEBI Angkatan 2022 UIN Sjech M. Djamil Djambek Bukittinggi - Arriny Fadillah; Baginda Parsaulian (Lembaga Yasin AlSys, 2026)
Although green lifestyle has received attention in various previous studies, studies that specifically discuss its influence on consumer behavior in purchasing eco-friendly products among Generation Z remain limited, particularly in the context of students at Islamic-based higher education institutions. This study aimed to analyze the influence of green lifestyle on consumer behavior in purchasing eco-friendly products among 2022 cohort FEBI students at UIN Sjech M. Djamil Djambek Bukittinggi. This study used a quantitative approach with a survey design. The research respondents were students selected using simple random sampling. Data were collected using questionnaires and interviews and were then analyzed using simple linear regression with SPSS 26. The results showed that green lifestyle had a positive and significant effect on consumer behavior, with a significance value of 0.000 < 0.05 and a coefficient of determination (R²) value of 0.702. This indicates that green lifestyle was able to explain 70.2% of the variation in consumer behavior in purchasing eco-friendly products. This finding contributes to the development of consumer behavior theory, particularly the Theory of Planned Behavior and Value-Belief-Norm Theory, and expands understanding of sustainable consumption behavior among Generation Z. Thus, green lifestyle is an important factor in shaping environmentally friendly consumption behavior, so educational institutions and business actors need to improve education and the provision of environmentally friendly products to encourage sustainable consumption practices.